Fabrication of Quercetin-Functionalized Morpholine and Pyridine Motifs-Laden Silk Fibroin Nanofibers for Effective Wound Healing in Preclinical Study - Govindaraj Sabarees; Vadivel Velmurugan; Siddan Gouthaman; Viswas Raja Solomon; Subramani Kandhasamy (MDPI AG, 2024)
Choosing suitable wound dressings is crucial for effective wound healing. Spun scaffolds with bioactive molecule functionalization are gaining attention as a promising approach to expedite tissue repair and regeneration. Here, we present the synthesis of novel multifunctional quercetin with morpholine and pyridine functional motifs (QFM) embedded in silk fibroin (SF)-spun fibers (SF-QFM) for preclinical skin repair therapies. The verification of the novel QFM structural arrangement was characterized using ATR-FTIR, NMR, and ESI-MS spectroscopy analysis. Extensive characterization of the spun SF-QFM fibrous mats revealed their excellent antibacterial and antioxidant properties, biocompatibility, biodegradability, and remarkable mechanical and controlled drug release capabilities. SF-QFM mats were studied for drug release in pH 7.4 PBS over 72 h. The QFM-controlled release is mainly driven by diffusion and follows Fickian's law. Significant QFM release (40%) occurred within the first 6 h, with a total release of 79% at the end of 72 h, which is considered beneficial in effectively reducing bacterial load and helping expedite the healing process. Interestingly, the SF-QFM-spun mat demonstrated significantly improved NIH 3T3 cell proliferation and migration compared to the pure SF mat, as evidenced by the complete migration of NIH 3T3 cells within 24 h in the scratch assay. Furthermore, the in vivo outcome of SF-QFM was demonstrated by the regeneration of fresh fibroblasts and the realignment of collagen fibers deposition at 9 days post-operation in a preclinical rat full-thickness skin defect model. Our findings collectively indicate that the SF-QFM electrospun nanofiber scaffolds hold significant capability as a cost-effective and efficient bioactive spun architecture for use in wound healing applications.